Biodiesel Production from Waste Cooking Oil Using Hydrodynamic Cavitation-Assisted Transesterification - Rizki Ulandari; Martomo Setyawan; Erna Astuti (Fakultas Teknologi Industri - Universitas Muslim Indonesia, 2026)
The global energy crisis and the depletion of fossil fuel reserves have intensified the demand for sustainable alternative energy sources. Biodiesel derived from waste cooking oil represents a promising renewable energy source that also promotes the utilization of waste materials without competing with food resources. This study investigates the intensification of biodiesel production from waste cooking oil through hydrodynamic cavitation-assisted transesterification. Unlike conventional transesterification systems, hydrodynamic cavitation enhances interfacial mass transfer, micro-mixing efficiency, and local shear intensity, thereby accelerating triglyceride conversion into fatty acid methyl esters (FAME). The effects of NaOH catalyst concentration (1% and 1.5% w/w oil) and cavitation cycle number (15, 23, 30, 38, and 45 cycles) on biodiesel yield and physicochemical properties were systematically evaluated. Biodiesel quality was assessed based on density and viscosity according to the Indonesian National Standard (SNI 7182:2015). The results demonstrated that increasing cavitation intensity and catalyst concentration generally improved biodiesel quality and yield. Biodiesel produced using 1.5% NaOH exhibited more stable density and viscosity values across different cavitation cycles and consistently satisfied SNI requirements. The optimum condition was achieved at 1.5% NaOH and 45 cavitation cycles, resulting in a biodiesel yield of 85.72%. Compared to conventional mixing-based transesterification reported in previous studies, the hydrodynamic cavitation-assisted process demonstrated enhanced reaction efficiency through intensified turbulence generation and improved mass transfer characteristics. These findings confirm the promising potential of hydrodynamic cavitation as a process intensification technology for sustainable biodiesel production from low-quality feedstocks.